2016
DOI: 10.1016/j.matbio.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene reduces skeletal fractures in an animal model of osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a genetic disease of Type I collagen and collagen-associated pathways that results in brittle bone behavior characterized by fracture and reduced mechanical properties. Based on previous work in our laboratory showing that raloxifene (RAL) can significantly improve bone mechanical properties through non-cellular mechanisms, we hypothesized that raloxifene would improve the mechanical properties of OI bone. In experiment 1, tibiae from female wild type (WT) and homozygous oim mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…Recently, our lab has shown that raloxifene significantly increases bone hydration and this is associated with improved mechanical properties, most notably post-yield parameters [19]. These effects have been noted both in vivo and in vitro, in mice, rats, dogs and humans [19,20,24,3335]. Since at least some of the effects from raloxifene are not cell-mediated, we hypothesized that treatment with raloxifene could significantly benefit the mechanical properties of bone in conditions such as bisphosphonate-treatment where the tissue becomes brittle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our lab has shown that raloxifene significantly increases bone hydration and this is associated with improved mechanical properties, most notably post-yield parameters [19]. These effects have been noted both in vivo and in vitro, in mice, rats, dogs and humans [19,20,24,3335]. Since at least some of the effects from raloxifene are not cell-mediated, we hypothesized that treatment with raloxifene could significantly benefit the mechanical properties of bone in conditions such as bisphosphonate-treatment where the tissue becomes brittle.…”
Section: Discussionmentioning
confidence: 99%
“…The dose and duration of ZOL was chosen as it has shown efficacy in suppressing remodeling and affecting mechanical properties in this genetic strain [21]. The lower dose of RAL has been used previously and shown efficacy in vivo [24]; a higher dose was arbitrarily chosen as 4× higher to determine if dose-responses could be quantified. At 24 weeks of age, animals were euthanized and the right femurs were removed, wrapped in saline-soaked gauze, and frozen (−20C) for later analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated an increase in bone healing by callus formation when teriparatide is combined with BMP-7, a recombinant protein in bones (Morgan et al, 2008). Raloxifene has been shown to decrease the rate of bone fractures in mice (Berman et al, 2016) and may prove to be useful to decrease fractures in future human trials of OI. Denosumab is an antibody currently used to prevent fractures in post-menopausal women with osteoporosis (Cummings et al, 2009; Shaker et al, 2015) and is being evaluated to treat OI.…”
Section: Osteogenesis Imperfectamentioning
confidence: 99%
“…Bones were tested to failure in 4 point bending (upper loading span of 3 mm, lower support span of 9 mm) in displacement control at a rate of 0.025 mm/s while hydrated with PBS. Using a custom MATLAB program 7 , structural and apparent material properties were determined. Apparent material properties were derived using standard beam-bending equations for four-point bending and geometric data from microCT.…”
Section: Do Bone Studies Need Placebos?mentioning
confidence: 99%